Influence of Product Quality and Price on Customer Satisfaction at Timezone - Akbar, Muh Irsyad Abror Putra Raja; Arif, Hery Maulana; Amalia, Rezki Yunika; Kasim, Amalia; Drajat, Muhammad Surya Toti (Economics and Business Journal (ECBIS), 2024)
Contemporary society's life is very dependent on entertainment. Some people choose to spend their free time in malls or shopping centers because of limited time and increasing busyness. One of these family entertainment centers is Timezone, which has outlets in several malls in Makassar city, such as Ratu Indah Mall, Panakkukang Mall, and Nipah Mall. And we focused our research on Timezone Mall Panakkukang. Timezone needs to improve itself to improve the quality of product so that customers are satisfied and can survive the competition. The research method used in this research is a quantitative method and distributes surveys to Timezone customers. The type of data used is primary data. This research used a non-purposive sample, with a sample size of 50 people. To test survey data for validity and effectiveness using SPSS (Statistical Package for the Social Sciences) using multiple linear regression. From the results of multiple linear regression it means that variables X1 (product quality) and X2 (product price) have no effect on variable Y (customer satisfaction timezone).